Precise Tuning of the D‑Band Center of Dual-Atomic Enzymes for Catalytic Therapy - Zeng, Ruijin; Gao, Qian; Xiao, Limei; Wang, Weijun; Gu, Yu; Huang, Hengshuo; Tan, Yingjun; Tang, Dianping; Guo, Shaojun (Journal of the American Chemical Society, 2024)
Single-atom nanozyme-based catalytic therapy is of great interest in the field of tumor catalytic therapy; however, their development suffers from the low affinity of nanozymes to the substrates (H2O2 or O2), leading to deficient catalytic activity in the tumor microenvironment. Herein, we report a new strategy for precisely tuning the d-band center of dual-atomic sites to enhance the affinity of metal atomic sites and substrates on a class of edge-rich N-doped porous carbon dual-atomic sites Fe–Mn (Fe1Mn1–NCe) for greatly boosting multiple-enzyme-like catalytic activities. The as-made Fe1Mn1–NCe achieved a much higher catalytic efficiency (K cat/K m = 4.01 × 105 S–1·M–1) than Fe1–NCe (K cat/K m = 2.41 × 104 S–1·M–1) with an outstanding stability of over 90% activity retention after 1 year, which is the best among the reported dual-atom nanozymes. Theoretical calculations reveal that the synergetic effect of Mn upshifts the d-band center of Fe from −1.113 to −0.564 eV and enhances the adsorption capacity for the substrate, thus accelerating the dissociation of H2O2 and weakening the O–O bond on O2. We further demonstrated that the superior enzyme-like catalytic activity of Fe1Mn1–NCe combined with photothermal therapy could effectively inhibit tumor growth in vivo, with an inhibition rate of up to 95.74%, which is the highest value among the dual-atom artificial enzyme therapies reported so far.